A novel capillary electrophoretic method for the analysis of dioxins and furans - Wan Ibrahim, Wan Aini (Faculty of Science, 2005)
Micellar electrokinetic chromatography (MEKC) is increasingly popular in the analysis of organic pollutants in the environment due to its high separation efficiency, less solvent usage and shorter analysis time. In this study, MEKC was used for the separation of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) and 2,3,7,8- tetrachlorodibenzo-p-furan (TCDF) with a separation buffer consisting of 20 mM sodium cholate, 20 mM sodium tetraborate decahydrate and 5% v/v organic modifier acetonitrile-methanol (3:1 v/v) at a final buffering pH of 9.16-9.22. Separation voltage was at 25 kV with anodic injection and optimum wavelength set at 225 nm. To improve the limit of detection (LOD), five on-line preconcentration techniques were evaluated. The techniques were normal stacking mode (NSM-MEKC), reversed electrode polarity stacking mode (REPSM-MEKC), high conductivity sample stacking mode (HCSSM-MEKC), sweeping and field enhanced sample injection (FESI-MEKC). High conductivity sample stacking method-MEKC (HCSSMMEKC) that gave an LOD of 46 ppb for TCDF and 18.5 ppb for TCDD was chosen. Solid phase disc extraction (SPDE) was used to further improve the LOD during the extraction of TCDF and TCDD from water thus reducing the LODs by 1000 fold. LODs in the ppt range were achieved for both analytes.